Institutional Distance and Location Choice of Multinational Enterprises - DU, Yumeng (Institutional Knowledge at Singapore Management University, 2009)
Even though scholars have realized the importance of the impact of the institutional environment on the strategy of MNEs, most of them have overlooked the first and essential step of the FDI decision location choice. In this paper, we link institutional theory and location choice literature and propose that the difference in the host country and home country`s institutional environments - institutional distance - has a negative effect on the FDI`s location choice. We also formulate hypotheses about firm specific attributes that may moderate this impact of institutional distance on location choice. Using data on Japanese companies` FDI information and the World Bank Governance indicator, we empirically test these ideas and the results show that the greater institutional distance significantly diminishes the MNE's intention to invest